Strategy to Restore Business Stability at PT. Edu - Salsabella Kanzu Watani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study investigates the decline in revenue of a company in the education technology (edtech) industry, PT. Edu, which resulted in the company cutting its budget, laying off employees, and reducing its marketing efforts. A qualitative method was used to identify internal and external challenges that affected the decline faced by PT. Edu with the aim of determining the root cause of the decline and formulating solutions. Several tools were used for data analysis, such as Marketing Mix 7Ps, VRIO, PESTEL, Porter's Five Forces, and SWOT. The author also used the TOWS Matrix to formulate the solutions presented in this study, which contain strategic recommendations for PT. Edu to restore its business stability.